Effect of Particle Coating on Matrix-Reinforcement Bonding - Shaiful Rizam Shamsudin; Mohd Fitri Mohamad Wahid; Shamsul Baharin Jamaludin, Assoc. Prof. Dr.; Khairel Rafezi Ahmad; Ruhiyuddin Mohd Zaki; A.G.B. Syamsul; M. Harun; Y. Hafizal (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.